Development of Acid-Soil Tolerant Corn (Zea mays L.) with High-Quality Protein - E.S. Halimi; N.R. Pransiswa; D.A. Purba (AGRIVITA, Journal of Agricultural Science, 2011)
Corn is an important food crop in Indonesia. Plant expansion has been hampered by soilacidity problem and the protein content of many corn varieties was low. This research initiates development of soil-acid-tolerant corn with highquality- protein content. Research was done on 12 factorial treatments and 3 replications as blocks in RCBD. The first factor was corn populations: Toray-1(G1), Toray-2(G2), GS- 5(G3) and GS-10(G4). The second factor was fertilizations: P1(69 kg N+36 kg P2O5+15 kg K2O per ha)); P2(115 kg N+54 kg P2O5+30 kg K2O per ha); and P3(161 kg N+72 kg P2O5+45 kg K2O per ha). The observed variables consisted of several agronomic traits, including the protein content. Results indicated that the corn populations, in general, showed good agronomic traits. The differences were mostly between populations, not between fertilizations, and no interaction was observed. The yield potential ranged from 4.25 to 6.47 ton dry seeds per ha. The protein content of seed resulted from cross ranged from 9.84% to 11.30%, as compared to the parents of 9.11% and 12.62%. This research concludes that genetic factors play an important role as confirmed by heritability estimate (h2)=0.75.Keywords : Corn, protein, acid-soil, tolerance